Effects of CIK Cell Therapy Combined with Camrelizumab on the Quality of Life in Patients with Nasopharyngeal Carcinoma and Analysis of Prognostic Factors. (9th May 2022) - Feng, Tao; Luo, Xiu; Cao, Wenping; Man, Rongjun; Feng, Xinrong; Song, Yujie
Abstract : Objective . To investigate the effects of CIK (cytokine-induced killer) cell therapy combined with camrelizumab on the quality of life in patients with nasopharyngeal carcinoma and prognostic factors. Methods . In this retrospective study, the materials of 80 patients with nasopharyngeal carcinoma treated in our hospital (February 2017–February 2019) were retrospectively analyzed, and they were equalized into experimental group ( n  = 40) and control group ( n  = 40) according to the order of admission. Both groups received 200 mg of camrelizumab on day 1 combined with 10 mg of anrotinib from day 2 to day 4. The patients received the above program every 3 weeks and 4 treatment cycles. The experimental group also received CIK cell therapy simultaneously. The patients' quality of life, immune indexes, local control, metastasis, and survival rate were compared between the two groups, and the prognostic factors were analyzed by logistic analysis. Results . Compared with the control group, the experimental group achieved much higher scores of physical well-being (18.38 ± 2.31), social/family well-being (16.40 ± 2.24), emotional well-being (15.35 ± 2.30), functional well-being (17.30 ± 2.20), and head and neck cancer subscale (15.40 ± 2.01, P  < 0.001) and eminently better immune indexes (P  < 0.001) after treatment. During the 24-month follow-up, there were 2 recurrent cases (5.0%) and 2 cases (5.0%) with distant metastasis among the 40 patients in the experimental group; there were 8 recurrent cases (20.0%) and 7 cases (17.5%) with distant metastasis among the 40 patients in the control group. In the experimental group, the median survival period was 18 months and the 2-year survival rate was 97.5% (39/40). In the control group, the median survival period was 14 months and the 2-year survival rate was 85.0% (34/40). Among the 80 patients, 7 cases (8.75%) died and 73 cases (91.25%) survived. After conducting the single-factor analysis, remarkable differences in the cases of IV stage, quality of life after treatment, and immune indexes after treatment between the survival group and the death group were observed (P  < 0.05). According to the multiple-factor analysis, the clinical stage and immune indexes were identified as the prognostic factors. Conclusion . CIK cell therapy combined with camrelizumab can enhance the life quality and immune function of the patients with nasopharyngeal carcinoma, thus improving their prognoses.